Bioactive secondary metabolites from endophytic strains of Neocamarosporium betae collected from desert plants - Liu, Peng; Tan, Yue; Yang, Jian; Wang, Yan-Duo; Li, Qi; Sun, Bing-Da; Xing, Xiao-Ke; Sun, Di-An; Yang, Sheng-Xiang; Ding, Gang (Frontiers in Plant Science, 2023)
Endophytic fungi inhabiting in desert plants belong to a group of unique microbial community with few chemical investigation, which could be new resources for bioactive natural products. In this report, thirteen secondary metabolites (1–13) with diverse carbon skeletons, including a novel polyketide (1) with a unique 5,6-dihydro-4H,7H-2,6-methanopyrano[4,3-d][1,3]dioxocin-7-one ring system, and three previously undescribed polyketides (2, 7, and 11), were obtained from two desert plants endophytic fungi Neocamarosporium betae. Different approaches including HR-ESI-MS, UV, IR, NMR and CD spectra were used to determine the planar and absolute configurations of these new molecules. The possible biosynthetic pathways were proposed based on structural characteristics of 1–13. Compounds 1, 3–4 and 9 exhibited strong cytotoxicity towards HepG2 cancer cell compared with positive control. In addition, several metabolites (2, 4–9 and 11–13) also displayed phytotoxic activities on foxtail leaves. The results further supported that endophytic fungi from special environments such as desert areas with poorly chemically investigated could produce bioactive new/novel secondary metabolites.